APLIKASI VALUE ENGINEERING PADA PEKERJAAN TAMBAH KURANG UNTUK MENINGKATKAN EFISIENSI BIAYA KONTRAKTOR (Studi Kasus: Gedung D BPOM Jakarta) - Hidayat, Indra; Wibowo, Kartono; Sumirin, Sumirin (Politeknik Negeri Semarang, 2024)
Cost planning is one of the important things in a development project, both for theproject owner and the implementing contractor. The contractor has a planned costtarget at the tender stage, however, changes in costs may occur during theimplementation period due to additional or less work and resulting in changes incosts. To be able to achieve the cost efficiency target, this can be done by carryingout value engineering. The stages of the value engineering method consist of theinformation stage, function analysis stage, creativity stage, evaluation stage,development stage and recommendation stage. The application of value engineeringin the BPOM Building D Construction Project can provide an increase cost and stillmaintain function. Contractor get cost efficiency of IDR 1,528,657,929,- or 2.52%,while the project owner gets a cost efficiency of IDR 1,182,279,319 or 1.66%.